Development of novel composite rejuvenators for efficient recycling of aged SBS modified bitumen. (15th June 2022) - Han, Xiaobin; Mao, Sanpeng; Xu, Shi; Cao, Zhilong; Zeng, Shangheng; Yu, Jianying
Highlights: Isocyanate terminated long chain active rejuvenators (ITLCARs) were prepared; Novel composite rejuvenators (NCRs) were developed; The molecular structures of aged SBS could be effectively restored by ITLCARs. The properties of aged SBS modified bitumen could be recovered by NCRs. Abstract: Efficient recycling of aged SBS modified bitumen (ASBS-MB) is one of the difficult problems in the field of pavement materials. In this study, isocyanate terminated long chain active rejuvenators (ITLCARs) for aged SBS were synthesized by the reaction of 2, 4-toluylene diisocyanate (TDI)/ hexamethylene diisocyanate (HDI) and hydroxyl terminated polybutadiene (HTPB), namely T-HTPB and H-HTPB. And T-HTPB/H-HTPB and aromatic hydrocarbon oil (AO) were combined to form novel composite rejuvenators (NCRs), which were used to restore the properties of ASBS-MB. Afterwards, the effects of NCRs on physical properties, rheological properties and molecular weight distribution of ASBS-MB were investigated. FTIR results showed that ITLCARs were successfully synthesized. The results of gel permeation chromatography showed that NCRs had advantages in restoring the molecular weight of ASBS-MB to the level of SBS-MB. And the physical performances of ASBS-MB could be regenerated to the level of original SBS modified bitumen (SBS-MB) by NCRs. The high-temperature complex modulus and rutting factor of rejuvenated SBS modified bitumen (RSBS-MB) recovered by NCRs were better than those restored only by AO. Meanwhile, the low-temperature complex modulus and fatigue factor of RSBS-MB recovered by NCRs still had greater low-temperature properties. And the results of bending beam rheometer test indicated that creep stiffness and m-value of RSBS-MB at −12 ℃ and −18 ℃ meet the requirements of Strategic Highway Research Program. This study provides a novel rejuvenation method for the efficient recycling of ASBS-MB.